Incorporating Qur’anic Interpretation Into Course Materials Of English For Business: A Students' Perspective - Setyaningrum, Anisah (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2021)
This paper aims at investigating the students’ perspectives toward incorporating qur’anic interpretation into course materials of English for Business. This study is a qualitative survey. The subject of the study were 20 students of English subject in Sharia Business Management Study Program, Islamic Economic and Business Faculty, State Islamic Institute of Kudus, Central Java, Indonesia. The data were collected by spreading the questionnaire to the students and asked them to fill it. Then, the Likert Scale was implemented in analyzing the data. Result of this study shows that students have positive perspectives toward incorporating qur’anic interpretation into course materials of English for Business.